Aktivitas Antioksidan Kolagen dari Kulit Ikan Patin (Pangasius sp.) dengan Enzim Bromelin Kasar Kulit Nanas (Ananas comosus L.): Antioxidant Activity of Collagen from the Skin of Pangas Catfish (Pangasius sp) with Crude Bromelain Enzyme of Pineapple Peel - Fitri Yanti; Niken Dharmayanti; Suryanti Suryanti (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Pangas catfish skin is one of fishery by-products containing certain compounds which have the potential to be used as an alternative source of collagen having antioxidant activity. The purpose of this study is to determine the antioxidant activity in collagen, so that it can be used as an antioxidant material. Collagen was made using crude bromelain enzyme from pineapple peel with an activity of 1.0 U/g in several stages, which were pretreatment, deproteinization, degrasing, and extraction, using factorial RAL with a combination of 3 hours, 3.5 hours and 4 hours and crude enzyme concentration of 0 ; 1.5% ; 2%. The results of the observations showed that the best solubility was obtained in the T3E2 treatment which was 98.96%. The best viscosity was 22.67 cP. The best acidity (pH) at T1.E2 was 6.73. The molecular weights α1, α2, β and ƴ were : 131.51 kDa, 110.48 kDa, 202.48 kDa and 243.93 kDa. The best antioxidant activity was in T1.E3 treatment, which was 20.45 ferrous sulfate/g.